Pengaruh Eubiotik sebagai Feed Additive untuk Meningkatkan Kinerja Pertumbuhan Ikan Gabus - Safitri, Efano Iga; Putri, Riski Ega; Lestari, Siti (Jurnal Ilmiah Pertanian dan Peternakan, 2024)
Purpose: This study aims to optimize the cultivation of snakehead fish (Channa striata) by improving feed efficiency and growth performance using alternatives to antibiotic growth promoters. Due to the government ban on antibiotic use in aquaculture, eubiotics have emerged as a potential solution. These non-nutritive feed additives enhance nutrient absorption, supporting better fish health and performance. Methodology: The experiment used a Completely Randomized Design (CRD) with four treatments and three replications each. The treatments included: K (control, no eubiotics), A (5 ml eubiotics/100g feed), B (10 ml/100g feed), and C (15 ml/100g feed). Results: The results showed that the use of eubiotics at a concentration of 15 ml/100g feed significantly improved absolute growth, growth rate, feed efficiency, Feed Conversion Ratio (FCR), and survival rate of snakehead fish. Treatment C consistently yielded the best performance outcomes across all indicators, indicating the effectiveness of higher-dose eubiotic supplementation. Conclusion: The addition of eubiotics at 15 ml/100g of feed is the most effective treatment for improving the growth and feed efficiency of snakehead fish. This strategy is beneficial in sustainable aquaculture practices where antibiotic use is prohibited. Limitations: This study was limited to controlled experimental conditions, and further field trials are needed to validate findings in different farming systems. Contribution: This research contributes to sustainable aquaculture by demonstrating that eubiotics are a viable alternative to antibiotics. Their inclusion in fish feed improves nutrient absorption, feed utilization, and overall fish growth performance.